2023
DOI: 10.3897/phytokeys.222.97087
|View full text |Cite
|
Sign up to set email alerts
|

Five new synonyms for Impatiens procumbens (Balsaminaceae) in China

Abstract: In the revision on the genus Impatiens L. in China, we found that there were synonyms amongst some species. Impatiens procumbens Franch. morphologically resembled I. reptans Hook.f., I. crassiloba Hook.f., I. ganpiuana Hook.f., I. atherosepala Hook.f. and I. rhombifolia Y.Q.Lu & Y.L.Chen. After a thorough morphological study, based on original literature, type specimens and field surveys, it was found that the above six species of Impatiens had no substantial differences in morphological characters and the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…I. yui is accepted as a synonym of I. uncipetala [35]. I. atherosepala, I. crassiloba, I. ganpiuana, I. reptans, and I. rhombifolia are accepted as synonyms of I. procumbens based on a related study by Huang et al [36]. Ruchisansakun et al [37], in their study of the Balsaminaceae in Myanmar, treated I. aureliana as a synonym of I. violiflora, but in their recent book, Impatiens of Thailand, they concluded that more taxonomic evidence is still needed for the revision of these two species.…”
Section: Species Diversity Of Balsaminaceae In Chinamentioning
confidence: 99%
“…I. yui is accepted as a synonym of I. uncipetala [35]. I. atherosepala, I. crassiloba, I. ganpiuana, I. reptans, and I. rhombifolia are accepted as synonyms of I. procumbens based on a related study by Huang et al [36]. Ruchisansakun et al [37], in their study of the Balsaminaceae in Myanmar, treated I. aureliana as a synonym of I. violiflora, but in their recent book, Impatiens of Thailand, they concluded that more taxonomic evidence is still needed for the revision of these two species.…”
Section: Species Diversity Of Balsaminaceae In Chinamentioning
confidence: 99%